A History of the Girl Formation, Education and Identity (Springer International Publishing, 2018)
This book is centered on the history of the girl from the medieval period through to the early twenty-first century. Authored by an international team of scholars, the volume explores the transition from adolescent girlhood to young womanhood, the formation and education of girls in the home and in school, and paid work undertaken by girls in different parts of the world and at different times. It highlights the value of a comparative approach to the history of the girl, as the contributors point to shared attitudes to girlhood and the similarity of the experiences of girls in workplaces across the world. Contributions to the volume also emphasise the central role of girls in the global economy, from their participation in the textile industry in the eighteenth century, through to the migration of girls to urban centres in twentieth-century Africa and China.